EXPLORING THE LINK BETWEEN OBESITY AND HYPOTHYROIDISM - Saqib Malik; Sadia Rehman; Farhat Naz; Rehman, Najma; Zainab Syed (Journal of Ayub Medical College Abbottabad, 2023)
Background: Obesity and hypothyroidism are two common clinical conditions that are often connected. This connection is now more important because of an exceptional rise in the prevalence of obesity around the world. Both of these conditions have a noteworthy impact on human health and well-being. The main objective of this study was to determine the frequency of hypothyroidism in obese patients presenting at Ayub Teaching Hospital, Abbottabad. Methods: This cross sectional study was carried out on 242 patients in the Department of Medicine of Ayub Teaching Hospital, Abbottabad from 1st March to 31st August 2022. SPSS version 23.0 was used for data analysis. Result: In this study 242 obese patients were included. Mean age of the patients was 39.55±9.361 years. Mean BMI was 41.62±8.099kg/m2 ranging from 31 to 61kg/m2, mean TSH level was 3.04±2.604mU/l, mean T4 level was 8.53±2.215pmol/L and mean T3 level was 1.2195±0.35795nmol/L .Out of total 242 patients, 34(14.0%) were male and 208(86.0%) were female patients. Patients found with overt hypothyroidism were 11(4.5%), subclinical hypothyroidism were 31(12.8%) and euthyroid were 200 (82.6%) Conclusion: The proportion of hypothyroidism among the obese patients was quiet less in our setup and not significantly associated with age and gender of the patients.